Improving Accessibility and Delivery of Healthcare Services to Underserved Children through Technology: A Comprehensive Approach of Literature Review - Wahyudi, Iwan; Sulaiman, lalu (THRIVE Health Science Journal, 2024)
This study investigates the use of technology to improve healthcare accessibility and delivery for children in underprivileged communities through article review comprehensively. A literature review with qualitative method that involved four distinct steps. In the initial stage, the search was conducted using Google Scholar (GS) and Scopus website. The second stage was filtering, which entails selecting the journals that will be examined. The last stage was analysis the articles, this analysis uses a 4-step PRISMA process to identify 123 articles published from 2019 to 2024 in Scopus journal. The review was evaluated the efficacy of telemedicine, mobile health applications, and wearable devices in monitoring and addressing children's health, while considering genetic predispositions and underlying medical issues that influence growth patterns. The research emphasizes the importance of a comprehensive strategy in evaluating child growth and development, utilizing health data to tailor interventions. Online systems, such as mobile phones and PDAs, can support healthcare workers in underserved rural areas. The integration of technology is essential for addressing unique challenges in underserved areas and ensuring access to high-quality healthcare services for all children. Current monitoring methods include regular check-ups, growth charts, and developmental screenings, with advancements in technology providing new tools like mobile health apps and wearable devices. Involving various stakeholders in the evaluation process is crucial, with participatory research focusing on community empowerment, ownership, and capacity building. Online systems offer efficient and accessible ways to track health data but may come with privacy concerns and data breach risks. The study focuses on the effectiveness of online systems for monitoring child health indicators, discussing data collection methods, sampling strategies, and ethical considerations. Findings reveal the need to address areas such as limited social interaction and incorporate interactive activities and group projects into online curriculum. Understanding the impact of online learning on students' health and well-being is crucial for tailoring approaches to ensure comprehensive support. The research findings have significant implications for child health policy and practice, emphasizing the importance of social connection and mental well-being in online learning environments.